The work-life balance and job satisfaction - Dias, Á.; Feixeira, C.; Pereira, L.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Services and Operations Management, 2022)
The promotion of an internal environment marked by a positive and stable context contributes to the employees sense of belonging to the organisation. As such, it is increasingly important to enhance commitment and professional satisfaction, and at the same time, allowing their employees to achieve a balance between their professional and personal life. Using a quantitative study based on a survey sample of 262 workers, our findings reveal that the organisational environment positively affects job satisfaction. Furthermore, results indicate a strong and relation between organisational engagement and employee satisfaction. However, no significant relationships were found between organisational commitment and between professional and personal life balance. It was also found that organisational commitment mediates the relation between the organisational environment and job satisfaction, but not the relation between organisational commitment and the balance between professional and personal.